Navigating the Patient with Heart Failure through the Health-care System – The Perspective of Hospital Nurses - Štemberger-Kolnik, Tamara; Filej, Bojana; Nemeš, Silva; Ljubič, Andreja (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Navigating the complex health-care system requires the patients to have comprehensive knowledge, active participation, and self-efficacy in health management to effectively engage in planned activities that include diagnosis, treatment, and rehabilitation, to ensure a high quality of life and successfully prevent disease-related complications. AIM: This study aims to investigate which activities nurses in hospital settings perform to support patients with heart failure to increase health literacy and navigate effectively through the health-care system. METHODS: Based on qualitative research, the data were collected through semi-structured interviews with 11 nurses from hospitals where patients with heart failure are treated. After reviewing and analyzing the transcribed interviews, a qualitative content analysis of the text followed. RESULTS: Based on an inductive approach, we first identified coding units, which were grouped into 10 subcategories, and these into five categories: General health literacy, digital literacy, communication health literacy, interprofessional collaboration, and navigation through the health-care system. We found that the treatment of patients with heart failure varies in Slovenian hospitals. CONCLUSION: Inequality in the treatment of patients between different hospitals highlights the need for a coordinated approach in the Slovenian health-care system. It is crucial to establish uniform national guidelines that would define treatment standards, ensure evidence-based patient care, and thus reduce the disparity in the quality of treatment between different medical institutions.